Anticholinergics and benzodiazepines on cognitive impairment among elderly with Alzheimer's disease: A 1 year follow-up study - Rewadee Jenraumjit (2020)
© 2019 The Author(s). Objective: Age-associated decline in central cholinergic activity makes older adults susceptible to harmful effects of anticholinergics (ACs). Evidence exists of an association between effects of AC medications on cognition. This retrospective cohort study examines how ACs affect cognition among older adults with Alzheimer's disease (AD) who received acetylcholine esterase inhibitors (AChEIs) over the course of 12 months. Results: A total of 133 (80% women, mean age 78.38 years, SD 7.4) were recruited. No difference in sex, age and comorbid diseases was observed between participants who took ACs, benzodiazepines (BZDs) and AChEIs. The most common prescribed ACs was quetiapine, being used for behavioral and psychological symptoms (BPSD). Multilevel analysis showed that the change of mental state examination scores were significantly predicted in the group using ACs (t (169), - 2.52, p =.020) but not with the groups using BZD (t (162), 0.84, p =.440). Evidence showed that older adults with Alzheimer's disease and exposed to ACs exhibited lower global cognitive scores than those without AC exposure. Using ACs could be a trade-off between controlling BPSD and aggravating cognitive impairment. Highlighting the awareness of the potential anticholinergic effect is important and may be the best policy.